The Southern Version of Cursor Mundi, Vol. V - Eldredge, Laurence M. (Ottawa Mediaeval Texts and Studies, 2000)
The medieval poem Cursor Mundi is a biblical verse account of the history of the world, offering a chronological overview of salvation history from Creation to Doomsday. Originating in northern England around the year 1300, the poem was frequently copied in the north before appearing in a southern version in substantially altered form. Although it is a storehouse of popular medieval biblical lore and a fascinating study in the eclectic use of more than a dozen sources, the poem has until now attracted little scholarly attention. This five-part collaborative edition presents the Arundel version of the poem with variants from three others. In addition it provides a discussion of sources and analogues, detailed explanatory notes, and a bibliography.